Tiktok's Stitch Trends As A Feature Of Citizens' Negation In Communication On Social Media - Juditha, Christiany; Darmawan, Josep J. (Jurnal Komunikasi, 2023)
One social media that is now very popular platforms is TikTok. Currenly active TikTok users in Indonesia are the second highest after the United States. TikTok servers not only as medium for marketing, branding, and self-existence, but also a medium full of negative content. One of prominent  features of TikTok is widely used to respond to viral cases. However, this feature has also facilitated the occurrence of debates lead to conflicts among users. The purpose of this study is to get an overview of the TikTok stitch trend as a negation feature in citizen communication on social media. Netnography is the method used in this research. This research concludes that generally the accounts' self-presentation makes Stitch's image optimal in responding to viral cases. Generally, they negate (deny) viral TikTok videos in the hope that their negation is the most correct. Meanwhile, recipients of the messages created through stitches tend to respond by creating their own stitches, and/or providing comments as a form of feedback. Another finding of viral content, that are considered controversial by netizens, tend to produce hate speech and comments, mutual insults and bullying. Stitch is a communication channel for conveying ideas, opinions, criticism without filters with content that is less controllable and makes it more trending.